Therapeutic Effects of Low-Level Laser on Male Infertility: A Systematic Review: Low-level laser and male infertility - Eghbaldoost, Amirreza; Salehi Mashhadsari, Seyed Pooria; Ghadirzadeh, Erfan; Ghoreifi, Alireza; Allameh, Farzad (Journal of Lasers in Medical Sciences, 2023)
Introduction: The objective of this study was to assess the effectiveness and safety of photobiomodulation (PBM) in the treatment of male infertility. Methods: We searched Google Scholar, PubMed, and the reference sections of relevant papers published from January 1, 2000 to September 23, 2022. We retrieved all publications related to the impact of PBM on male infertility. After reviewing the titles, abstracts, and full texts, we included fifteen papers in the research. The studies involved 477 semen samples (in vitro studies) and 70 male participants (randomized clinical trials). Results: All 14 in vitro studies that evaluated effectiveness reported that PBM was successful in increasing the proportion of progressive sperms in semen samples. Various methods were used to evaluate the safety. One study with a sample size of 58 concluded that PBM was not a safe treatment, whereas the other ten studies confirmed its safety. Only one clinical trial evaluated the effect of laser acupuncture on male infertility and found improvements in sperm progressive motility without any serious adverse effects. Conclusion: All 15 studies evaluating effectiveness reported that the low-level laser was effective for increasing the proportion of progressive sperm in semen samples and that it was safe to use. However, due to the heterogeneity of population characteristics, source characteristics, duration of exposure, sample size, and instruments for measuring safety and efficacy, we cannot conclude that the positive results obtained from the reviewed studies are solely attributable to the low-level laser on the sperm samples.